Structural and Functional Diversity of Animal Toxins Interacting With GPCRs - Van Baelen, Anne-Cécile; Robin, Philippe; Kessler, Pascal; Maïga, Arhamatoulaye; Gilles, Nicolas; Servent, Denis (Frontiers in Molecular Biosciences, 2022)
Peptide toxins from venoms have undergone a long evolutionary process allowing host defense or prey capture and making them highly selective and potent for their target. This has resulted in the emergence of a large panel of toxins from a wide diversity of species, with varied structures and multiple associated biological functions. In this way, animal toxins constitute an inexhaustible reservoir of druggable molecules due to their interesting pharmacological properties. One of the most interesting classes of therapeutic targets is the G-protein-coupled receptors (GPCRs). GPCRs represent the largest family of membrane receptors in mammals with approximately 800 different members. They are involved in almost all biological functions and are the target of almost 30% of drugs currently on the market. Given the interest of GPCRs in the therapeutic field, the study of toxins that can interact with and modulate their activity with the purpose of drug development is of particular importance. The present review focuses on toxins targeting GPCRs, including peptide-interacting receptors or aminergic receptors, with a particular focus on structural aspects and, when relevant, on potential medical applications. The toxins described here exhibit a great diversity in size, from 10 to 80 amino acids long, in disulfide bridges, from none to five, and belong to a large panel of structural scaffolds. Particular toxin structures developed here include inhibitory cystine knot (ICK), three-finger fold, and Kunitz-type toxins. We summarize current knowledge on the structural and functional diversity of toxins interacting with GPCRs, concerning first the agonist-mimicking toxins that act as endogenous agonists targeting the corresponding receptor, and second the toxins that differ structurally from natural agonists and which display agonist, antagonist, or allosteric properties.